The role of social media in shaping public opinion - Shamilishvili, Inga; Sabashvili, Gvantsa ("Intercultural Dialogues" Transactions, 2023)
Mass communication plays an important role in shaping public opinion. Journalism aims to collect, process, and distribute information through various mass communications. Even in the early years, predecessors tried to spread information through various means. Modern approaches have allowed us to change the ways of information dissemination. The modern world has led to the formation of digital media. Digitization has simplified the acquisition, study, processing and analysis of information. The above mentioned processes have formed the social media platform. Digitalization has led to the popularity of social media platforms. The research of the Georgian media space showed us that objective approaches still remain a big challenge. Basically, the Georgian social media space is busy with propaganda, disinformation, hate speech, exposure of personal life and various challenges. Social media allows us to understand and analyze the real world more. Through social media, each individual becomes a communicator who, by spreading information, creates a new story and allows society to evaluate the said news itself. Of course, the purpose of social media is to find a target audience. Social media has somehow blurred the line between freedom of expression and media ethics. The digital space allows each media organization to convey information openly and objectively. During the study of the research topic, a modern approach to information reporting, which contradicts the principles of media ethics, was clearly identified. Mass communication, whose unconditional purpose is to inform the public with accurate and unbiased information, is often criticized because it can be subject to bias, manipulation and the spread of disinformation. Developing media literacy skills, knowledge of information sources, and engaging in diverse media consumption play a critical role in the effective advancement of mass communication. Based on the above, mass communication is presented as a link between society and individuals, providing a platform for sharing ideas, raising awareness and public advocacy.